Heavy Metal Contamination Status in Seven Fish Species from Reservoirs of Polonnaruwa District, Sri Lanka - Wijesinghe, H.; Idroos, F.S.; Manage, P.M. (Sri Lanka Journal of Aquatic Sciences, 2018)
Attached

Heavy metal contamination in aquatic ecosystems has become an emerging environmental issue. The stable physicochemical properties of heavy metals could result in bioconcentration and bioaccumulation in different organs of freshwater fishes. The present study records the accumulation of Lead (Pb), Cadmium (Cd), Chromium (Cr), Copper (Cu) and Zinc (Zn) in the head, muscle and skin regions of seven fish species namely, Labeo rohita, Oreochromis mossambicus, Oreochromis niloticus, Etroplus suratensis, Heteropneustes fossilis, Oligolepsis acutipennis and Puntius dorsalis collected from Minnerya, Parakrama Samudraya and Kaudulla reservoirs in Polonnaruwa district, Sri Lanka. The results showed that both Pb and Cd accumulated in high concentrations in the head region compared to the skin and muscles of the fish samples. The highest amounts of Pb (22.44±5.48 mg/Kg) and Cd (4.98±0.86mg/Kg) were recorded from the head parts of the H. fossilis in Minneriya and O. niloticus in Kaudulla respectively, whereas the highest amount of Cr (30.87±4.51mg/Kg) was detected in head part of the O. acutipennis in Minneriya. The Cu concentration was the highest (2.92±0.001 mg/Kg) in head regions of H. fossilis from Minneriya. Zn was the most abundant heavy metal detected in the head, muscle and skin regions of fish in all three reservoirs. The highest amount of Zn (118.93±10.55mg/Kg) was detected in the head part of O. acutipennis from Minneriya. The Pb, Cd, Cr, Cu and Zn concentrations detected in the head part of popular edible freshwater species, O. mossambicus, O. niloticus and E. suratensis were higher than the provisional tolerable weekly intake (PTWI) of Pb (0.025 mg/Kg), Cd (0.007 mg/Kg), Cr (0.1 mg/Kg), Cu (3.5 mg/Kg) and Zn (7 mg/Kg) specified by the FAO/WHO. Therefore, long-term consumption of these fish species especially the head parts may lead to accumulation of these heavy metals in tissues and lead to chronic diseases which may risk the health of consumers especially in the north-central province of Sri Lanka.
Keywords: bioaccumulation; edible fish; Head; heavy metal; muscles; skin